A case of celiacomesenteric trunk in combination with bilateral duplication of renal arteries and hypospadias - Pryakhin, Alexey; Khanna, Jugesh; Nandakumar, Harikrishnan; Haftkowycz, Peter; Kano, Gabriel (International Journal of Research in Medical Sciences, 2016)
A celiacomesenteric trunk, with common origin of the celiac and superior mesenteric arteries from the aorta, is quite rare. This variation may be accompanied by some other arterial anomalies, as well as being involved in pathological processes. We report the case of common celiacomesenteric trunk in combination with bilateral duplication of the renal arteries and hypospadias. Two large branches of celiacomesentric trunk were observed: the gastrosplenic and hepatomesenteric trunks. The gastrosplenic trunk was divided into the splenic artery and the left gastric artery. The hepatomesenteric trunk gave off the common hepatic artery and then was continuous as superior mesenteric artery. Bilateral duplication of the renal arteries, hypospadias and chordee were also presented. The embryological mechanism of celiacomesenteric trunk development is known. The association of the common celiacomesenteric trunk with bilateral duplication of renal arteries and anomalies of external genitalia (hypospadias) has not been reported. Knowledge about variations of arteries, particularly about the possibility of the celiacomesenteric trunk, is clinically important.